2018
DOI: 10.1371/journal.pone.0200270
|View full text |Cite
|
Sign up to set email alerts
|

Utility of high b-value (2000 sec/mm2) DWI with RESOLVE in differentiating papillary thyroid carcinomas and papillary thyroid microcarcinomas from benign thyroid nodules

Abstract: PurposeThe aim of the study was to evaluate the role of high b-value (2000 sec/mm2) diffusion-weighted imaging (DWI) by using Readout Segmentation of Long Variable Echo-trains (RESOLVE) in differentiating papillary thyroid carcinomas (PTCs) and papillary thyroid microcarcinomas (PTMCs) from benign thyroid nodules.Materials and methodsConsecutive patients with thyroid nodules scheduled for surgery underwent high b-value DWI with 3 b-values: 0, 800 and 2000 sec/mm2. Signal intensity ratios (SIRs) of thyroid nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…The mathematical model and parameter algorithm for DWI are calculated based on the Gaussian distribution of water diffusion, which does not conform to the true diffusion of water molecules in biological tissue. The lesions displayed by DWI are closely associated with the b-value [29, 30]. When b is less than 1000 s/mm 2 , water movement in the tissue seems to conform to the Gaussian distribution, since some minor factors that hamper water movement is difficult to detect, such as cell membranes and organelles.…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical model and parameter algorithm for DWI are calculated based on the Gaussian distribution of water diffusion, which does not conform to the true diffusion of water molecules in biological tissue. The lesions displayed by DWI are closely associated with the b-value [29, 30]. When b is less than 1000 s/mm 2 , water movement in the tissue seems to conform to the Gaussian distribution, since some minor factors that hamper water movement is difficult to detect, such as cell membranes and organelles.…”
Section: Discussionmentioning
confidence: 99%
“…It may reveal the heterogeneity of lesions, and thus ensure more accurate discrimination. Readout Segmentation of Long Variable Echo‐trains (RESOLVE) based on the reacquisition scheme is a relatively new approach to DWI, which reduces susceptibility artifacts and blurring from T 2 * signal decay, and it may improve the substantial reduction in image distortion compared with conventional single‐shot echo‐planar imaging (SS‐EPI) . Moreover, DWI with a high b ‐value ( b > 1000 s/mm 2 ) was introduced along with improvements in MRI gradient technology.…”
mentioning
confidence: 99%
“…According to the fitting curve of the mathematical model, higher b values were believed to better approximate the true diffusion in the tissue. Wang et al [39] reported that using the ADC value with the highest b value (2000 s/mm 2 ) to differentiate benign from malignant tumours of the thyroid yielded a sensitivity of 96.15% and a specificity of 85.48%, indicating that a DWI sequence with a long acquisition time (14 min) may not be desirable for widespread use. In our research, the sensitivity and specificity of the D value in the W-L ROIs were 95.45 and 91.67%, respectively; the DWI sequence required approximately 5 min.…”
Section: Discussionmentioning
confidence: 99%